Landfast Ice and Coastal Wave Exposure in Northern Alaska. Issue 22 (23rd November 2021) - Hošeková, Lucia; Eidam, Emily; Panteleev, Gleb; Rainville, Luc; Rogers, W. Erick; Thomson, Jim
Abstract: Observations of ocean surface waves at three sites along the northern coast of Alaska show a strong correlation with seasonal sea ice patterns. In the winter, ice cover is complete, and waves are absent. In the spring and early summer, sea ice retreats regionally, but landfast ice persists near the coast. The landfast ice completely attenuates waves formed farther offshore in the open water, causing up to a two‐month delay in the onset of waves near shore. In autumn, landfast ice begins to reform, though the wave attenuation is only partial due to lower ice thickness compared to spring. The annual cycle in the observations is reproduced by the ERA5 reanalysis product, but the product does not resolve landfast ice. The resulting ERA5 bias in coastal wave exposure can be corrected by applying a higher‐resolution ice mask, and this has a significant effect on the long‐term trends inferred from ERA5. Plain Language Summary: Ocean waves facilitate coastal erosion in the Arctic (and worldwide). Wave energy reaching Arctic coasts is controlled by seasonal sea ice, which includes landfast ice attached to the coastlines or sea floor, and mobile pack ice further seaward. Wave energy in the Arctic is increasing due to the loss of pack ice, and these effects are generally well‐represented in regional climate models. Landfast ice continues to form at the coast each year; when it lasts longer than pack ice, it provides protection against wave erosion. However, landfast ice is difficult to include in models which can lead them to overestimate the wave energy reaching the coasts. Using observations of waves from three coastal sites in Alaska, we demonstrate the importance of including landfast ice into regional models, and propose an effective method of combining public datasets to account for its effects on waves. These results can help the research community predict how much wave energy will be available for coastal erosion processes in the coming decades. Key Points: Year‐long observations show a seasonal cycle of wave exposure at three sites along the Arctic coast of northern Alaska The persistence of landfast ice in the late spring/early summer dramatically reduces the wave energy reaching the coast Coastal protection by landfast ice is not represented in global climate models, but it can be parameterized